Overview of the charging situation for digital contents in Japan: From the viewpoint of compensation for private sound and visual recording - Naonori Kato; Hiroki Nogawa; Masahi Ueda (International Telecommunications Society (ITS), 2011)
Japanese copyright law consists of two parts. One has to do with the rights of the content holder. The other is concerned with limitations to the rights of the content holder, such as compensation for private sound and visual recording; that is, charges for copying media where it is difficult to charge individually, as is the case with Digital Rights Management (DRM ). Such compensation permits the holders of the content to collect royalties through a special compensation arrangement. That is, the designated management associations impose the obligation for compensation on the manufacturers of recording devices. Despite the spread of such compensation arrangements, new challenges continue to arise, such the case of SARVH, the designated management association, brought against Toshiba, a manufacturer of DVD recorders. The Tokyo District Court ruled, 'Compensation is not required under copyright law, but just that all possible efforts be made.' It remains unclear whether holders of content can receive sufficient royalties or not. An analysis of the latest decision regarding digital content, from the point of copyright law, clarifies the relationship between DRM and compensation for private sound and visual recording. To accommodate stakeholders' requirements, a new regulation or structure for payment of royalties is proposed.
Keywords: 330; copyright law; DRM (Digital Rights Manegement); compensation; levy